Synthesis, Characterization and Antibacterial Study of Co(II), Ni(II), Mn(II) and Cu(II) Complexes Derived from 1,5-Dimethyl-4-{[1-(3-methyl-5-oxo-1-phenyl-4,5-dihydro-1H-pyrazol-4-yl-idene)ethyl]amino}-2-phenyl-1H-pyrazol-3(2H)-one - Zhu, Hualing; Chen, Chen; Wang, Junbin; Wei, Zhen; Bai, Yanan (Asian Journal of Chemistry, 2012)
Co(II), Ni(II), Mn(II) and Cu(II) complexes derived from 1,5-dimethyl-4-{[1-(3-methyl-5-oxo- 1-phenyl-4,5-dihydro-1H-pyrazol-4-yl-idene)ethyl]amino}-2-phenyl-1H-pyrazol-3(2H)-one have been prepared and characterized by elemental analysis, spectroscopic data (IR and UV) and H NMR. The antibacterial activity tests of the ligand and its metal complexes at different concentrations against Escherichia coli and Bacillus subtilis were performed by using disc diffusion method. The results indicate that almost all the compounds have the activity of inhibiting the growth of the two bacteria.